The Importance of the Natural Environment in the Light of Children's Rights With Particular Regard to Hungary - Kui Biborka (Magistra Iadertina, 2023)
The 2030 Agenda for Sustainable Development is based on human rights, and children’s rights need to be interpreted in this context. As the 2030 Agenda declares that the sustainable development goals seek to realise the human rights of all, it is important to include and interpret the rights of the child as a part thereof. The comprehensive and ambitiously worded goals in the Agenda for Sustainable Development are difficult to transpose into any binding conventions or tools in the area of human, and thus especially children’s, rights. One goal could be to manage these goals and targets within the existing international framework of law and children’s rights. Children’s rights are a comparatively new branch of law. The rules pertaining to the special, vulnerable situation of children were first written down approximately 100 years ago. At the time, the only goal was the survival of the child: feeding, clothing, and medical care. The content of rules and regulations has gradually broadened, and now children’s rights are considered one of the most progressively developing areas of human rights. The purpose of this study is to closely examine the legal regulations, conventions, studies, publications, essays, and historical descriptions pertaining to children, and to examine the degree to which they deal with the role of the natural environment in the life of the child, and how these regulations recognise and necessitate the essential role played by the natural environment in the physical, spiritual, intellectual, and moral development of children. One of the main pillars in this process is environmental education, or Education for Sustainable Development (ESD), and considering the current social circumstances, it is both necessary and expected to promote the ESD to the greatest extent possible. Taking the above into account, it can be seen that the provisions stating children’s rights do not clearly and unequivocally deal with the importance of the constant presence of the natural environment, while the right of the child to have fresh air and be raised in a natural environment is not suitably emphasised, even though it is an essential condition for the healthy physical, spiritual, intellectual, and moral development of the child.